2015
DOI: 10.7554/elife.06481
|View full text |Cite|
|
Sign up to set email alerts
|

Recruitment of the default mode network during a demanding act of executive control

Abstract: In the human brain, a default mode or task-negative network shows reduced activity during many cognitive tasks and is often associated with internally-directed processes, such as mind wandering and thoughts about the self. In contrast to this task-negative pattern, we show increased activity during a large and demanding switch in task set. Furthermore, we employ multivoxel pattern analysis and find that regions of interest within default mode network are encoding task-relevant information during task performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
178
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(224 citation statements)
references
References 25 publications
39
178
6
1
Order By: Relevance
“…These regions are reliably activated in the absence of a task (i.e., resting-state fMRI sessions; for review, see [6]), though it is unlikely that the DMN is a purely task-negative network [7][8][9]. The DMN is also involved in autobiographical planning and internally guided thoughts [10,11].…”
Section: Mind Wandering and The Brainmentioning
confidence: 99%
“…These regions are reliably activated in the absence of a task (i.e., resting-state fMRI sessions; for review, see [6]), though it is unlikely that the DMN is a purely task-negative network [7][8][9]. The DMN is also involved in autobiographical planning and internally guided thoughts [10,11].…”
Section: Mind Wandering and The Brainmentioning
confidence: 99%
“…Second, intracranial electrophysiology studies of DMN areas have shown increased activity immediately at the offset of task performance, perhaps too rapidly to reflect mind-wandering (49). Third, fMRI studies with unique task paradigms suggest that under certain contexts, increased DMN activity occurs during cognitive processes that may involve aspects of externally oriented attention (17,18,50). Finally, studies of spontaneous prestimulus activity suggest nuanced relationships of DMN activity with attentional performance (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although the DMN is commonly deactivated during externally oriented tasks requiring cognitive control (15), older adult populations report low levels of mind-wandering during task performance yet exhibit attenuated DMN deactivation (16). Additionally, in certain contexts, increased DMN activity is time-locked to stimulus changes in the external environment (17,18).Although spontaneous increases of DMN activity are postulated to reflect mind-wandering, a highly consistent finding is that DMN activity is higher when ongoing behavior is stable rather than variable (19-21). This finding would be counterintuitive if there were a one-to-one mapping between mind-wandering intensity and DMN activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No published study has directly tested for these competing alternatives within a single experiment, and other hypotheses have been proposed in the interim, such as, for instance, that the DMN is driven by significant revisions of cognitive context, regardless of whether it the context is externally or internally focused (Crittenden, Mitchell, and Duncan, 2015).…”
Section: Intentionality-based Imagination (Recollective/social)mentioning
confidence: 99%